CHARACTERISTIC OF CONTRACTION AND DISCHARGE COEFFICIENT FOR FLOW UNDER SLUICE GATE - Sunik Sunik (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2020)
The contraction coefficient (Cc) and discharge coefficient (Cd) always rise in flow while sluice gate operated with variation of open gate and discharge (Q). This experimental research used prototype model made from fiberglass (horizontal channel), sluice gate installed on it. Two models of trapezoid baffle block installed as three rows, specified location 25 cm after sluice gate pair using sill with different dimension. Water depth (y) and velocity (v) were measured during each running test then Froude number, contraction coefficient (Cc) and discharge coefficient (Cd) were calculated. The result showed that trapezoid baffle block model T2 (used no sill, sill 2 cm and sill 2.7 cm, Fr = 0.11 - 0.75) gives the better performance modelling of Cc and Cd in term of the initial Froude number with R2 = 0.8086 (Cc) and R2 = 0.8273 (Cd).